Antioxidant and anti-tyrosinase activities of piper caninum extract and pure compounds - Farediah Ahmad, Farediah (2011)
Malaysia is rich in biodiversity and there are many potential medicinal plants yet to be explored. The piper family is widely used by the locals to treat a variety of illnesses. The aim of this study was to evaluate the biological activities of Piper caninum extract and purified compound. Piper caninum was extracted using methanol (extract: PCM), ethyl acetate (extract, PCEA) and hexane (extract, PCH). Three compounds were purified, identified and named: pc1_UTM, pc2_UTM and pc3_UTM. Both compounds and extracts were tested for antioxidant activities using DPPH scavenging assay, ferric-reducing antioxidant power (FRAP) and total phenolic content using Folin-Ciocalteu reagent. Anti-tyrosinase activities were also evaluated. The IC50 values revealed that pc1_UTM has the highest activities followed by pc2_UTM, pc3_UTM, PCEA and PCM mean while PCH was negative. PCEA exerted the highest percentage of tyrosinase inhibitor followed by PCM and PCH with values of 68.47%, 64.15% and 61.08% respectively. Meanwhile, pc3_UTM had the highest antityrosinase activity (44.15%) followed by pc2_UTM (42.96%) and pc_utm1 (32.95%) for compounds. The study suggested that Piper caninum provides a source of natural antioxidants and anti-tyrosinase agents and may be beneficial to human health. Presently, further studies on the molecular basis of the anti-inflammatory properties are carried out for the compounds.